Regulation of Apoptosis During Porcine Circovirus Type 2 Infection - Pan, Yuhong; Li, Pengfei; Jia, Renyong; Wang, Mingshu; Yin, Zhongqiong; Cheng, Anchun (Frontiers in Microbiology, 2018)
Apoptosis, an indispensable innate immune mechanism, regulates cellular homeostasis by removing unnecessary or damaged cells. It contains three signaling pathways: the mitochondria-mediated pathway, the death receptor pathway and the endoplasmic reticulum pathway. The importance of apoptosis in host defenses is stressed by the observation that multiple viruses have evolved various strategies to inhibit apoptosis, thereby blunting the host immune responses and promoting viral propagation. Porcine Circovirus type 2 (PCV2) utilizes various strategies to induce or inhibit pro-grammed cell death. In this article, we review the latest research progress of the apoptosis mechanisms during infection with PCV2, including several proteins of PCV2 regulate apoptosis via interacting with host proteins and multiple signaling pathways involved in PCV2-induced apoptosis, which provides scientific basis for the pathogenesis and prevention of PCV2.